The issue of the hybrid regime genesis in Venezuela (1999–2013) - G. E. Ludena Lopez (Управление)
The article gives the author’s interpretation of the genesis of Venezuela political system during the presidency of Hugo Chavez (1999–2013). In the article, when considering the hybrid regime proposed by Guillermo O’Donnell, an attempt was made to analyze the transformation of the political system with the advent of democracy in Venezuela, in which the author highlights the features and democratic or authoritarian aspects inherent in the government from democracy in Venezuela in 1958. The constitutional orders of 1961 and the new Constitution of 1999 constitute the fundamental legal foundations of the entire democratic process that has existed from 1958 to the present, which, obviously, in a historical perspective, points to the trinity of law, power and force, manifested in such historical moments, like overthrowing Perez Jimenez. On the basis of the conducted historical and documentary research, the author of the article concludes that the hybrid regime established by H. Chavez in the first five years of his reign became more and more authoritarian over time. According to the author of the article, the peculiarity of the Chavez administration is that not only legal, regulatory and informal instruments aimed at restricting freedom of expression and assembly, hindering the emergence of democratic pluralism, but also repressive measures.